2019
DOI: 10.1002/ente.201900722
|View full text |Cite
|
Sign up to set email alerts
|

Drying of Lithium‐Ion Battery Anodes for Use in High‐Energy Cells: Influence of Electrode Thickness on Drying Time, Adhesion, and Crack Formation

Abstract: When fabricating battery electrodes, their properties are strongly determined by the adjusted drying parameters. This does not only affect their microstructure in terms of adhesion, but also influences cell performance. The reason is found to be the binder transported to the surface during drying. Herein, it is shown that when thicker electrodes are processed, new challenges arise. On the one hand, loss of adhesion associated with certain drying conditions becomes a more serious problem; on the other hand, cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
151
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(154 citation statements)
references
References 32 publications
2
151
0
1
Order By: Relevance
“…In particular, the adhesive forces as well as the ionic and electrical conductivity are important electrode properties, which must be preserved in electrode design and processing. [1][2][3][4][5][6] To handle the insufficient adhesion problem at low binder content, some approaches use multilayer electrodes with binder and additive gradients. [7][8][9][10] One approach, which is used in this work, is to apply a very thin primer layer to the current collector to significantly improve the adhesive force in combination with a low binder content in the active layer (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the adhesive forces as well as the ionic and electrical conductivity are important electrode properties, which must be preserved in electrode design and processing. [1][2][3][4][5][6] To handle the insufficient adhesion problem at low binder content, some approaches use multilayer electrodes with binder and additive gradients. [7][8][9][10] One approach, which is used in this work, is to apply a very thin primer layer to the current collector to significantly improve the adhesive force in combination with a low binder content in the active layer (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant increase in mass loading (up to 12 mg/cm 2 ) neglects the positive influence of very high temperatures [171]. Kumberg et al [140] studied drying rates (from 0.75 to 15.5 g/m 2 s) and compared state-of-the-art anode coating thicknesses (75 µm) or mass loadings (2.2 mAh/cm 2 ) to those of higher thickness or loadings (300 µm or 9.35 mAh/cm 2 ). Drying rates up to 3 g/m 2 s were possible without cracking even for anodes six times thicker (450 µm) than the state-of-the-art (75 µm), although binder diffusion was still a problem.…”
Section: The Convective Drying Parameters and The Resulting Electrochemical Performancementioning
confidence: 99%
“…During the coating step, the slurry is applied with a fixed thickness onto an Al foil or Cu foil for cathodes or anodes, respectively. However, a high thickness can lower the cohesion strength between particles and the adhesion strength between the current collector and coated layer [140]. Finding a balance between thickness and mechanical integrity is crucial for obtaining a high-capacity electrode with high cycling stability.…”
Section: Coating Techniques: the Electrode Thickness And Its Mechanical Strengthmentioning
confidence: 99%
“…[ 2,9 ] To the authors knowledge, research exists that either simulates drying behavior of lithium‐ion electrodes or investigates it experimentally. [ 6,10 ] The comparison of experiments under defined and industrially relevant drying conditions with simulation though has so far not been realized. The major challenge is the experimental setup that has to allow for industrially relevant drying conditions and render in situ measurements possible at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…At one point, first pores within the structure begin to empty and the film ends to shrink, reaching the end of film shrinkage (EOF) and the second drying stage. [ 2,5,6 ] Using cryogenic scanning electron microscopy experiments, it was found that capillary transport is the governing mechanism transporting solvent to the electrodes surface during the second drying stage, supposedly carrying the binder along. [ 5 ] These experiments though are very complex and based on single measurements, which is why further research is needed to establish new and easy ways to illuminate the drying process.…”
Section: Introductionmentioning
confidence: 99%